CX3CL1-induced CD16+ monocytes extravasation in myeloperoxidase-ANCA-associated vasculitis correlates with renal damage - Tang, Jiale; Liao, Zhonghua; Luo, Liying; Deng, Shuanglinzi; Jiang, Yuanyuan; Wang, Fangyuan; Hu, Xinyue; Yin, Hongling; Gong, Guanghui; Feng, Juntao; Li, Xiaozhao (Frontiers in Immunology, 2022)
Background: Monocytes are involved in the pathogenesis of ANCA-associated vasculitis (AAV). Monocyte/macrophages are the dominant infiltrating cells in the glomeruli of patients with myeloperoxidase-AAV (MPO-AAV). However, how human monocyte subsets extravasate to the kidney in MPO-AAV with renal damage is unclear. Methods: 30 MPO-AAV patients with renal damage and 22 healthy controls were enrolled in this study. Monocyte subsets and monocyte-related chemokines in the blood and kidneys of MPO-AAV patients were detected. The chemoattractant activity of the CX3CL1-CX3CR1 axis on CD16+ monocytes was observed. The effect of MPO-ANCA on the migration of CD16+ monocytes to human glomerular endothelial cells (HGECs) was detected by flow cytometry and transwell migration assay. Results: Compared with controls, CD16+ monocytes were significantly decreased in the blood and increased in the glomeruli of MPO-AAV patients with renal damage. The level of CX3CL1, but not CCL2, was significantly increased in the plasma of MPO-AAV patients. CX3CL1 co-localized with glomerular endothelial cells in MPO-AAV patients with renal damage. Moreover, we initially found that MPO-ANCA promotes an increase of the chemokine CX3CL1 on HGECs, imposing recruitment on CD16+ monocytes. Finally, the percentage of CD16+ monocytes in the blood was found to be negatively correlated with proteinuria, while the infiltration of CD16+ monocytes into the kidney was positively correlated. Conclusion: Enhanced extravasation of CD16+ monocytes to the kidney via the CX3CL1-CX3CR1 axis may be involved in renal damage in MPO-AAV.